PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 015 TALANG JERINJING - Dwi Indriyani; Mahmud Alpusari; Damanhuri Daud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Study of IPA in SD expected can push student to be active and feel like to know. In study of student activity less, teacher tend to monoton, still use discourse so that result of learning student of low. Complication this research internal issue that is what is skill of teacher, student activity, and result learn student can mount to applying Model Study of Cooperative Type Make A Match Class V SDN 015 Talang Jerinjing ?. Model Make a Match represent one solution to overcome the problem it. Destination this research isdescription skill of teacher, student activity and improve result learn student in study of IPA class student V SDN 015 Talang Jerinjing through applying model of Make a Match. Model Make a Match developed peculiarly to increase student activity by exploiting problem card and answer as media play at the same time this study.Represent research of class action with planning step, execution of action, and observation of reflection. Research subject is class student and teacher of V SDN 015 Talang Jerinjing. Technique gathering of data use tes and nontes. Result of research show skill of teacher at cycle of I obtain get score 17 category enough, at cycle of II get score 20 with category very good. Student cycle activity of I get totally of score 13 with category enough later then mount at cycle of II get totally of score 19,5 with good category. Result learn natural student of improvement. Cycle of I student average value equal to 79,11 with percentage of classical 66,67%, cycle of II average value mount to become 83,89 with percentage of classical 77,77%. Pursuant to result of research can be concluded that model of cooperativ type of Make a Match expressed to succeed. Suggestion to teacher better more creative again in creating immeasurable game so that student feel to like and more interest to follow activity study of type cooperative of Make a Match do not only applied in study of just IPA but at other subject. This matter because of besides can improve student activity, this model also can uplift skill teacher and result learn.Keyword : Model study type cooperative of Make a Match , Result Learn IPA